PEMETAAN PENELITIAN CUKAI DI INDONESIA - Hanik Susilawati (JURNAL PERSPEKTIF BEA DAN CUKAI, 2023)
This study aims to map research on excise tax in Indonesia. This research is a qualitative research with a bibliographical approach. Researchers used a sample of 42 articles published in 2007 to 2022 in accredited national journals. Based on the results of the mapping, the most published articles are in Sinta 4 (40.48%), with the research object of tobacco product excise (61.90%), with the topic of the impact of implementing excise (47.62%), and using the qualitative method (57.14%). Based on the research results, the direction of research on excise in the future can be expanded to other types of excise besides tobacco excise. The research theme on the impact of excise duty is still relevant, in addition to the need for studies on expanding the excise base with the option of new excise types. Research with quantitative methods can also be reproduced.